Peripheral Administration of NMU Promotes White Adipose Tissue Beiging and Improves Glucose Tolerance - Yue Yuan; Hongdong Wang; Jielei He; Haixiang Sun; Dalong Zhu; Yan Bi (International Journal of Endocrinology)
Purpose. Targeting white adipose tissue (WAT) beiging has been proposed as an effective way to increase thermogenesis and improve glucose metabolism. Neuromedin U (NMU) is a neuropeptide that could increase energy expenditure, while its effects on WAT beiging and glucose homeostasis remain to be investigated. Methods. Male C57BL/6 mice were fed with high fat diet (HFD) to induce obesity and hyperglycemia and then treated with chronic subcutaneous injection of NMU. Body weight and food intake were recorded daily. After 14 days of injection, intraperitoneal glucose tolerance tests and 18F-fluorodeoxyglucose micro-positron emission tomography/computed tomography (18F-FDG micro-PET/CT) scans were conducted. Subcutaneous WAT (sWAT) and interscapular brown adipose tissue were collected for the evaluation of adipocyte size, expression of uncoupling protein 1 (Ucp1), and other thermogenic-related genes. Stromal vascular fraction of subcutaneous WAT was extracted for the measurement of type 2 innate lymphocytes (ILC2s) proportions. Results. Glucose tolerance was markedly improved by peripherally administered NMU. Micro-PET/CT suggested that NMU promoted WAT beiging, which was further confirmed by haematoxylin and eosin (H&E) staining and immunohistochemistry. In diet-induced-obese (DIO) mice, NMU activated thermogenic-related genes in WAT. In addition, NMU stimulated ILC2s in the stromal vascular fraction of WAT. Conclusion. Taken together, our study indicates that peripheral administration of NMU is a potential therapeutic strategy for the promotion of WAT beiging and the improvement of impaired glucose tolerance.